The tongue of the red panda (Ailurus fulgens fulgens Cuvier, 1825)-a stereoscopy, light microscopy and ultrastructural analysis - Goździewska-Harłajczuk, Karolina; Hamouzová, Pavla; Klećkowska-Nawrot, Joanna; Čížek, Petr (PeerJ, 2021)
In the light of recent molecular studies, there are two phylogenetic species of the red panda (Ailurus fulgens): Ailurus fulgens fulgens and Ailurus fulgens styani. The red panda belongs to the endangered species living in the wild only in Asia and is included in the CITES list. Although the biology and diet of this species has been extensively described, the histological structure of the tongue and lingual glands has not yet been characterized in detail in relation to the lifestyle of this mammal under specific conditions and as a basis for comparative anatomical studies of the biodiversity of endemic species. Study samples were collected from two adult males of Ailurus fulgens f. held in Wrocław Zoological Garden. Both tongues were examined macroscopically; moreover, samples with lingual papillae for light microscopy and scanning electron microscopy (SEM) were collected from the apex, body and root of the tongue. Both tongues of the Ailurus fulgens f. males were approximately 9 cm long. The dorsal lingual surface was covered with mechanical and gustatory lingual papillae. Filiform papillae were observed on the apex and the body of the tongue, while small conical papillae were observed on the root of the tongue. An elongated, 1-1.5 cm long cylinder-shaped lyssa was observed in the ventral part of the apex. Moreover, most numerous and largest round in shape fungiform papillae were observed on the apex and on the border of the body and root of the tongue, located directly rostrally to 12-13 round and oval in shape vallate papillae. The SEM study showed that filiform papillae on the apex had several long secondary processes, while filiform papillae on the body of the tongue were taller and their secondary papillae were shorter than the equivalent structures on the apex of the tongue. The SEM study showed numerous taste pores on the surface of the fungiform papilla, while irregular surface of the vallate papillae, however some of them had smoother surface. Mixed glands (comprised of mucous acini and serous acini) were present within the vallum (within the connective tissue core) of the vallate papilla. Beneath the papillae more serous glands were observed, while the posterior lingual glands in the caudal part of the root of the tongue were mucoserous (mucous units were prevalent). A characteristic feature of the tongue of Ailurus fulgens f. was the presence of lyssa, which is comparable to other representatives of Carnivora, but the number of vallate papillae was individually variable. The lack of strongly developed mechanical conical papillae probably may be related to the type of plant food that is particularly dominant in red panda. Further differences between Ailurus fulgens f. and Ailurus fulgens s. cannot be excluded. The results of these studies may be useful especially for veterinarians specializing in working with exotic animals and people dealing with wildlife conservation.
Keywords: Histochemistry; Scanning electron microscopy; Histology; Lingual papillae; Diet; Highly selective forager; Microstructure; Ailurus fulgens f.